Approaching the Lithiation Limit of MoS2 While Maintaining Its Layered Crystalline Structure to Improve Lithium Storage. (20th February 2019) - Zhu, Zhiqiang; Tang, Yuxin; Leow, Wan Ru; Xia, Huarong; Lv, Zhisheng; Wei, Jiaqi; Ge, Xiang; Cao, Shengkai; Zhang, Yanyan; Zhang, Wei; Zhang, Hongwei; Xi, Shibo; et al.
Abstract: MoS2 holds great promise as high‐rate electrode for lithium‐ion batteries since its large interlayer can allow fast lithium diffusion in 3.0–1.0 V. However, the low theoretical capacity (167 mAh g −1 ) limits its wide application. Here, by fine tuning the lithiation depth of MoS2, we demonstrate that its parent layered structure can be preserved with expanded interlayers while cycling in 3.0–0.6 V. The deeper lithiation and maintained crystalline structure endows commercially micrometer‐sized MoS2 with a capacity of 232 mAh g −1 at 0.05 A g −1 and circa 92 % capacity retention after 1000 cycles at 1.0 A g −1 . Moreover, the enlarged interlayers enable MoS2 to release a capacity of 165 mAh g −1 at 5.0 A g −1, which is double the capacity obtained under 3.0–1.0 V at the same rate. Our strategy of controlling the lithiation depth of MoS2 to avoid fracture ushers in new possibilities to enhance the lithium storage of layered transition‐metal dichalcogenides. Abstract : Durch Feinabstimmung der Lithiierungstiefe von MoS2 kann die kristalline Schichtstruktur beim Zyklisieren (3.0–0.6 V gegen Li + /Li) bewahrt werden, einhergehend mit einer Vergrößerung des Abstands zwischen den Schichten. Dies ermöglicht ein stabiles Zyklisieren von kommerziellem μm‐großem MoS2 mit höherer Kapazität und Lade/Entlade‐Rate; man erhält damit eine vielversprechende Anode für schnellladende Lithium‐Ionen‐Batterien.